A Statistical quality control study on NFF industrial corporation - Castro, Carlo (College of Engineering, 2004)
NFF Industrial Corporation (NFFIC), the company under study, strives to continually improve to be in the forefront of the competition. Its main product is the flexible bulk bag. The company's goal of fully serving the demand of industrial products for both local and export markets calls for a great challenge. To achieve this goal, the company gives great effort to maintain or improve the quality of products they manufacture. The group aims to analyze and generate recommendations on the factors affecting the rejection of flexible bulk bags. Inspections and rejections are made during raw materials inspection and testing, after-cutting process, and after sewing process. The team then focused on three stages of rejection using Pareto Analysis and utilized an Ishikawa Diagram to each identify the probable causes of rejection. The first problem concerns the rejection of raw materials (Polypropylene Sheets). Three characteristics are important in the acceptance of PP sheets. Specific weight, tensile strength, and maximum allowable temperature. Statistical process control was conducted by constructing the x-bar and R chart for each characteristic for the data of the year 2001. The chart for the specific weight was found to be out of control while the charts for tensile strength and maximum allowable temperature was found to be in control. Process Capability Analysis results suggested that the capability of the vendor to meet specifications of the company is inadequate. To address this, it was recommended that the company implement SPC to each supplier to aid in vendor selection. AS detailed implementation and estimated additional quality costs were prepared.It was also recommended that the company construct a covered storage area for the raw materials stored outside because of warehouse space unavailability.